Antimicrobial-Resistant Enterococcus spp. in Wild Avifauna from Central Italy - Giulia Cagnoli; Fabrizio Bertelloni; Paolo Interrante; Renato Ceccherelli; Margherita Marzoni; Valentina Virginia Ebani (MDPI AG, 2022)
Bacteria of the genus Enterococcus are opportunistic pathogens, part of the normal intestinal microflora of animals, able to acquire and transfer antimicrobial resistance genes. The aim of this study was to evaluate the possible role of wild avifauna as a source of antimicrobial-resistant enterococci. To assess this purpose, 103 Enterococcus spp. strains were isolated from the feces of wild birds of different species; they were tested for antimicrobial resistance against 21 molecules, vancomycin resistance, and high-level aminoglycosides resistance (HLAR). Furthermore, genes responsible for vancomycin, tetracycline, and HLAR were searched. E. faecium was the most frequently detected species (60.20% of isolates), followed by E. faecalis (34.95% of isolates). Overall, 99.02% of the isolated enterococci were classified as multidrug-resistant, with 19.41% extensively drug-resistant, and 2.91% possible pan drug-resistant strains. Most of the isolates were susceptible to amoxicillin/clavulanic acid (77.67%) and ampicillin (75.73%), with only 5.83% of isolates showing an ampicillin MIC ≥ 64 mg/L. HLAR was detected in 35.92% of isolates, mainly associated with the genes ant(6)-Ia and aac(6')-Ie-aph(2")-Ia. Few strains (4.85%) were resistant to vancomycin, and the genes vanA and vanB were not detected. A percentage of 54.37% of isolates showed resistance to tetracycline; tet(M) was the most frequently detected gene in these strains. Wild birds may contribute to the spreading of antimicrobial-resistant enterococci, which can affect other animals and humans. Constant monitoring is essential to face up to the evolving antimicrobial resistance issue, and monitoring programs should include wild avifauna, too.